Palliative and end of life care for children and young people : home, hospice, and hospital - Grinyer, Anne, 1950-; Wiley eBooks (Chichester, West Sussex, UK ; Ames, Iowa, USA : Wiley-Blackwell, 2012)
"This topical and timely text provides valuable insights into the choices and experiences of palliative and end of life care for young people with cancer and other life limiting illnesses. With a focus on palliative care provision across a range of different clinical settings, this comprehensive new resource explores care in the home, the hospice and hospital. It looks at how and where families and young people can access palliative care, and what support is offered to attain their preferred place of death. Bereavement support for families is discussed, as well as a discussion of multi-disciplinary work, interagency co-operation and resource issues. This will be essential reading for community children's nurses, specialist palliative care teams, children's hospices, school nurses, social workers and student nurses as well as families"--Provided by publisher.
Palliative and end of life care for children and young adults -- Home-based palliative and end of life care -- Hospice-based palliative and end of life care -- Hospital-based palliative and end of life care -- Preparation for the end of life, bereavement, and emotional support -- The implications for policy and practice.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Terminally ill children -- Care; Palliative Care; Terminal Care; Adolescent; Child; Continuity of Patient Care; Hospice Care; Young Adult; Palliative treatment; Medicine; MEDICAL -- Nursing -- Pediatric & Neonatal; Terminally ill children -- Care; Electronic books